The effect of different tooth extraction patterns on Bolton index and occlusal relationship of skeletal Class Ⅱ malocclusion - SONG Ye, REN Yinting, ZHANG Yihan, HAN Jingying (Editorial Office of Stomatology, 2024)
Objective To investigate the effect of different premolar extraction patterns on Bolton index and occlusal relationship of skeletal Class Ⅱ malocclusion. Methods The plaster models of 62 patients with skeletal Class Ⅱ malocclusion were selected and converted into digital models by iTeroElement scanner. Each model was simulated by the four premolar extraction pattrens, and tooth arrangement test was performed after tooth extraction. The Bolton index before and after tooth extraction was calculated, and the occlusal relationship after tooth arrangement was evaluated to explore its law. Results All the four premolar extraction patterns resulted in a significant decrease in the Bolton index over-all ratio in skeletal Class Ⅱ patients, and compared with the extraction patterns of 4/4 and 4/5, the patterns of 5/4 and 5/5 resulted in a greater decrease in the Bolton index over-all ratio(P<0.001). For skeletal class Ⅱ malocclusion, the tooth arrangement test was conducted on the basis of establishing the neutral relationship of first molar. The average value of anterior teeth over-jet obtained by patterns of 4/4 and 4/5 was within the normal range(<3 mm). The average value obtained by patterns of 5/4 and 5/5 was greater than the normal range(>3 mm), and the difference was statistically significant(P<0.001). Conclusion The premolar extraction patterns of 4/4 and 4/5 are more conducive to normalizing the Bolton index over-all ratio and establishing the better occlusal relationship for skeletal Class Ⅱ malocclusion.